2015
DOI: 10.1016/j.vaccine.2015.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E vaccine immunization for rabbits to prevent animal HEV infection and zoonotic transmission

Abstract: Hepatitis E virus (HEV) infection has become a significant global public health concern as increasing cases of acute and chronic hepatitis E are reported. HEV of animal origin was proved to be a possible source of human infection and a previous study showed that the recent licensed HEV 239 vaccine can serve as a candidate vaccine to manage animal sources of HEV infection. However, previous immunization strategy for rabbits was the same as that for human, which is too costly to conduct large-scale animal vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 62 publications
1
19
0
2
Order By: Relevance
“…Recently, a recombinant HEV genotype 1 vaccine (Hecolin®) has been approved by the Chinese Food and Drug Administration in China . This vaccine induces HEV‐specific antibodies in 100% of vaccinated healthy individuals resulting in protection against homologous (genotype 1) and in part against heterologous (genotypes 2–4) HEV infections in humans and animal studies . The efficiency of protection is dependent on the antibody level prior HEV infection .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a recombinant HEV genotype 1 vaccine (Hecolin®) has been approved by the Chinese Food and Drug Administration in China . This vaccine induces HEV‐specific antibodies in 100% of vaccinated healthy individuals resulting in protection against homologous (genotype 1) and in part against heterologous (genotypes 2–4) HEV infections in humans and animal studies . The efficiency of protection is dependent on the antibody level prior HEV infection .…”
Section: Introductionmentioning
confidence: 99%
“…Liver and kidney tissues were collected from R1 for histopathology and immunohistochemistry. Detailed methods have been described previously 4. Positive/negative-stranded HEV RNA was detected in the kidneys, indicating virus replication in the tissue.…”
mentioning
confidence: 99%
“…The healthy laboratory rabbit is easy to access and economic for use in large-scale experiments 4 5. Moreover, we have previously demonstrated that the rabbit is susceptible to HEV-44 5 and a 22-week chronic-type infection was observed when infected with a swine HEV-4 strain 4. Future experiments will determine the infectious dose that can establish stable chronic HEV-3 infection in the rabbit model and investigate whether rabbit model can also be used to study chronic infection with HEV-4.…”
mentioning
confidence: 99%
“…A WHO reference standard for anti‐HEV antibody (NIBSC ref 95/584, 100 IU/ml) [Ferguson et al, ] was provided by Wantai Biopharmaceutical, Inc. (Beijing, China). The candidate anti‐HEV antibody serum RS26 (rabbit serum 26 as the standard serum in this study) was collected from a rabbit vaccinated with two 20 µg doses of HEV 239 vaccine at week 0 and 4 [Zhang et al, ]. These and all other sera were tested for the presence of anti‐HEV antibody with a commercial HEV‐specific sandwich ELISA assay as previously described [Wang et al, ; Liu et al, ].…”
Section: Methodsmentioning
confidence: 99%